Tokyo junkie : 60 years of bright lights and backstage shadows - Whiting, Robert (Stone Bridge Press, 2021)
This book recounts six decades of life in Tokyo, blending memoir with social history. It traces the city's transformation from postwar ruins to a global metropolis, highlighting its politics, culture, baseball scene, and nightlife through the perspective of a long-term foreign resident.